2016
DOI: 10.1103/physrevlett.117.056403
|View full text |Cite
|
Sign up to set email alerts
|

Slater to Mott Crossover in the Metal to Insulator Transition ofNd2Ir2O7

Abstract: We present an angle-resolved photoemission study of the electronic structure of the three-dimensional pyrochlore iridate Nd_{2}Ir_{2}O_{7} through its magnetic metal-insulator transition. Our data reveal that metallic Nd_{2}Ir_{2}O_{7} has a quadratic band, touching the Fermi level at the Γ point, similar to that of Pr_{2}Ir_{2}O_{7}. The Fermi node state is, therefore, a common feature of the metallic phase of the pyrochlore iridates. Upon cooling below the transition temperature, this compound exhibits a gap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 58 publications
7
70
0
Order By: Relevance
“…4d,f. Interestingly, the WSM phase, which was theoretically predicted to exist in quite a narrow temperature window at zero field67 and hence would be difficult to detect such an electronic band state by optical36 and angle-resolved photoemission spectroscopy37, can be extended by an application of magnetic field along [001], which deforms the regular 4/0 spin configuration. Moreover, as the pressure increases, both AIAO insulating phase and WSM one appear to shrink, whereas the LSM extends towards zero temperature and zero field.…”
Section: Resultsmentioning
confidence: 99%
“…4d,f. Interestingly, the WSM phase, which was theoretically predicted to exist in quite a narrow temperature window at zero field67 and hence would be difficult to detect such an electronic band state by optical36 and angle-resolved photoemission spectroscopy37, can be extended by an application of magnetic field along [001], which deforms the regular 4/0 spin configuration. Moreover, as the pressure increases, both AIAO insulating phase and WSM one appear to shrink, whereas the LSM extends towards zero temperature and zero field.…”
Section: Resultsmentioning
confidence: 99%
“…We speculate that the observed behavior can be attributed to the emergence of a Mott insulator (see e.g. [67]), placing the system beyond the FCQPT point in the phase diagram. At the same time, in the case of herbertsmithite, the transport and thermodynamic properties suggest that the gapless state represented by the SCQSL is situated before FCQFT.…”
Section: Dynamic Relaxation and Heat Transport Propertiesmentioning
confidence: 94%
“…The magnetically ordered pyrochlores, such as A=Eu, Nd are seen, in clean samples, to be insulating at low temperatures Tafti et al, 2012;Tian et al, 2016;Ueda et al, 2012Ueda et al, , 2015b. The metallic phase above the magnetic ordering temperature is expected have quadratic doubly degenerate bands that touch at the Γ point (Kondo et al, 2015;Nakayama et al, 2016;Witczak-Krempa and Kim, 2012), a state we term a Luttinger semimetal (Abrikosov and Beneslavskii, 1971a;Moon et al, 2013). In A=Pr, which remains a nonmagnetic metal down to low temperatures (Machida et al, 2010;Nakatsuji et al, 2006), a quadratic band touching has been found recent experiments (Kondo et al, 2015) (See Sec.…”
Section: Magnetic Weyl Semimetalsmentioning
confidence: 99%